The first near-linear bis(amide) f-block complex: a blueprint for a high temperature single molecule magnet. Issue 1 (10th November 2014) - Chilton, Nicholas F.; Goodwin, Conrad A. P.; Mills, David P.; Winpenny, Richard E. P.
Abstract : An unprecedented near-linear bis(amide) f-element complex has been prepared by utilizing bulky silylamide ligands. This Sm(ii ) complex is a blueprint for the next generation of single molecule magnets, where predictions for the Dy(iii ) analogue suggest they could operate above 77 K. Abstract : We report the first near-linear bis(amide) 4f-block compound and show that this novel structure, if implemented with dysprosium(iii ), would have unprecedented single molecule magnet (SMM) properties with an energy barrier, U eff, for reorientation of magnetization of 1800 cm −1 .